Red blood cells tracking and cell-free layer formation in a microchannel with hyperbolic contraction: A CFD model validation. (November 2022) - Gracka, Maria; Lima, Rui; Miranda, João M.; Student, Sebastian; Melka, Bartłomiej; Ostrowski, Ziemowit
Highlights: Euler-Lagrange (E-L) model allows to track erythrocytes position in microchannel. Euler-Euler model allows determining the red blood cells distribution in domain. E-L approach pointed out better prediction of the RBCs behavior in simulations. The numerical model permits to test many types of channels without producing them. Contraction width results in different sized CFL downstream of the narrowing. Abstract: Background and Objective: In recent years, progress in microfabrication technologies has attracted the attention of researchers across disciplines. Microfluidic devices have the potential to be developed into powerful tools that can elucidate the biophysical behavior of blood flow in microvessels. Such devices can also be used to separate the suspended physiological fluid from whole in vitro blood, which includes cells. Therefore, it is essential to acquire a detailed description of the complex interaction between erythrocytes (red blood cells; RBCs) and plasma. RBCs tend to undergo axial migration caused by occurrence of the Fåhræus-Lindqvist effect. These dynamics result in a cell-free layer (CFL), or a low volume fraction of cells, near the vessel wall. The aim of the paper is to develop a numerical model capable of reproducing the behavior of multiphase flow in a microchannel obtained under laboratory conditions and to compare two multiphase modelling techniques Euler-Euler and Euler-Lagrange. Methods: In this work, we employed a numerical Computational Fluid Dynamics (CFD) model of the blood flow within microchannels with two hyperbolic contraction shapes. The simulation was used to reproduce the blood flow behavior in a microchannel under laboratory conditions, where the CFL formation is visible downstream of the hyperbolic contraction. The multiphase numerical model was developed using Euler-Euler and hybrid Euler-Lagrange approaches. The hybrid CFD simulation of the RBC transport model was performed using a Discrete Phase Model. Blood was assumed to be a nonhomogeneous mixture of two components: dextran, whose properties are consistent with plasma, and RBCs, at a hematocrit of 5% (percent by volume of RBCs). Results: The results show a 5 μ m thick CFL in a microchannel with a broader contraction and a 35 μ m thick CFL in a microchannel with a narrower contraction. The RBC volume fraction in the CFL is less than 2%, compared to 7–8% in the core flow. The results are consistent for both multiphase simulation techniques used. The simulation results were then validated against the experimentally-measured CFL in each of the studied microchannel geometries. Conclusions: Reasonable agreement between experiments and simulations was achieved. A validated model such as the one tested in this study can expedite the microchannel design process by minimizing the need to prefabricate prototypes and test them under laboratory conditions.